Food consumption rates of piscivorous brown trout (Salmo trutta) foraging on contrasting coregonid prey. (29th June 2015) - Jensen, H.; Kahilainen, K. K.; Vinni, M.; Gjelland, K. Ø.; Malinen, T.; Harrod, C.; Amundsen, P.‐A.
Abstract Knowledge of predator–prey dynamics is essential to understand ecosystem functioning. Quantification of such interactions is important for fisheries management, in particular in the case of stocking programmes. Here, food consumption rates (FCR) were quantified for wild and stocked piscivorous brown trout, Salmo trutta L., in three subarctic lakes with contrasting coregonid (Coregonus spp.) prey communities, using the Wisconsin and the Elliott–Hurley bioenergetic models. FCR was highest for stocked brown trout in lakes with the lowest predator densities, and lowest for wild brown trout. Although FCR estimate may vary somewhat depending on the specific model used, such tools are imperative for the proper impact assessment of brown trout stocking programmes and for the provision of advice on optimal stocking densities.